Design and Validation of STEM Integrated e-Modules on Environmental Pollution to Improve Problem-Solving Skills - Fernandu, Dina Else; Abdurrahman, Abdurrahman; Lengkana, Dewi (Jurnal Pendidikan MIPA, 2022)
Scientific literacy about awareness and problem-solving skills related to environmental issues is one of the competencies that must be instilled in students in science learning in the future. However, teaching materials that have the potential to instill these competencies have not been easily accessed by students. The purpose of this study was to design and validate an integrated electronic module with a STEM approach on environmental pollution materials to improve problem-solving skills. This research uses Research and Development (R&D) method with ADDIE (Analysis, Design, Development, Implementation, Evaluation). The E-Module is designed for Project-Based learning (PJBL-STEM) with steps of Reflection, Research, Discovery, Application and Communication. The results of construct validation obtained a percentage of 89.4%, content validation yielded a percentage of 95% and language validation 91.7% with all very valid criteria. Based on the pre-test and post-test trials of the use of e-modules carried out on students, it was found that the N-gain was 0.40 with problem-solving criteria moderate for students. Overall, the research show that the developed e module is validated with a very valid category and can improve students problem-solving skills. Keywords: e-module, STEM, PjBL, problem-solving skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp754-765